Paper-based analytical devices for virus detection: Recent strategies for current and future pandemics - Ozer, Tugba; Henry, Charles S. (ELSEVIER SCI LTD, 2021)
The importance of user-friendly, inexpensive, sensitive, and selective detection of viruses has been highlighted again due to the recent Coronavirus disease 2019 (COVID-19) pandemic. Among the analytical tools, paper-based devices (PADs) have become a leading alternative for point-of-care (POC) testing. In this review, we discuss the recent development strategies and applications in nucleic acid based, antibody/antigen-based and other affinity-based PADs using optical and electrochemical detection methods for sensing viruses. In addition, advantages and drawbacks of presented PADs are identified. Current state and insights towards future perspectives are presented regarding developing POC diagnosis platform for COVID-19. This review considers state-of-the-art technologies for further development and improvement in PADs performance for virus detection. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Paper-based; Virus detection; COVID-19; SARS-CoV-2; Point of care; Infectious diseases; Optical; Electrochemical; Nanomaterials; LATERAL-FLOW ASSAY; POINT-OF-CARE; ELECTROCHEMICAL DNA-BIOSENSORS; NUCLEIC-ACID AMPLIFICATION; MICROFLUIDIC DEVICES; HEPATITIS-B; ARTIFICIAL-INTELLIGENCE; SENSITIVE DETECTION; RAPID DETECTION; ZIKA VIRUS; Chemistry